IMPLEMENTASI KEBIJAKAN PELAYANAN PUBLIK SISTEM ELEKTRONIK DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA SUKABUMI - Tuah Nur; Kalinda Oktafiani; Riky Nuryaman (LPPM UNSAP, 2026)
This study analyzes the implementation of electronic-based public service policies through the Moci Legit application at the Sukabumi City Population and Civil Registration Office. Digital transformation in the population administration service sector is expected to improve efficiency, transparency, and public access. However, in practice, various obstacles remain, including system disruptions, limited service information, and the continued occurrence of manual processes following online submissions. The study employs a descriptive qualitative approach using observation, interviews, and documentation techniques. Analysis utilizes Edwards III’s policy implementation model, which encompasses communication, resources, disposition, and bureaucratic structure. The results of the study indicate that policy implementation is underway but has not yet been optimized. The main inhibiting factors include the capacity of the application system, limitations in the public’s digital literacy, and internal coordination that has not yet been fully integrated. The study recommends strengthening digital infrastructure, enhancing the capacity of government officials, and improving electronic complaint mechanisms.